Overgrowth Syndromes-Evaluation, Diagnosis, and Management - Joshua Manor; Seema R. Lalani (Frontiers Media S.A., 2020)
Abnormally excessive growth results from perturbation of a complex interplay of genetic, epigenetic, and hormonal factors that orchestrate human growth. Overgrowth syndromes generally present with inherent health concerns and, in some instances, an increased risk of tumor predisposition that necessitate prompt diagnosis and appropriate referral. In this review, we introduce some of the more common overgrowth syndromes, along with their molecular mechanisms, diagnostics, and medical complications for improved recognition and management of patients affected with these disorders.